Consumption of hair dye products by the French women population: Usage pattern and exposure assessment. (February 2016) - Bernard, A.; Houssin, A.; Ficheux, A.S.; Wesolek, N.; Nedelec, A.S.; Bourgeois, P.; Hornez, N.; Batardière, A.; Misery, L.; Roudot, A.C.
Abstract: Only few published data are available in the literature about consumption and exposure, for hair dye products. The aim of this study was to assess the use of 10 different hair dye products in French Women with a focus on consumption of hair dye in different places of use (at home and at the hairdressers) in order to assess the corresponding dermal exposures. The assessment was performed on a total of 4237 women older than 15 years old, thanks to three national web surveys. The percentage of hair dye users among the French women population was about 64%.The mean frequency of use ranged between 2.23 and 14.22 times per year depending on the studied product and age category of women. This study provided the first data available for exposure to hair dye products with mean exposures ranging between 1.48 and 6.49 mg/kg bw/day depending on the product studied and age category of women. Moreover, consumption data obtained in this study might be useful to perform safety assessment of hair dye products thanks to the knowledge of the age categories of the population having the highest percentage of users and/or frequency of use. Highlights: The use of hair dye products in French women was assessed with a focus on consumption in different places of use. French women consumers older than 15 years old were taken into account. This study provided data on the percentage of hair dye users, frequency of use and quantity used per application. French women external dermal chronic exposure to hair dye products was assessed in mg/kg bw/day.